Improving Language Development Through Story Book Media in Early Childhood - Nurjannah Nurjannah; Batmang; Karim (Lambaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2024)
Based on the situation that occurs in PAUD Bombana Regency, children's language skills are still relatively lacking, this is because teachers at PAUD do not apply interesting learning media. Improving children's language skills is very important to help the growth and development of children specifically in further education. So, this research aims to find out (1) an overview of children's language abilities using storybook media in early childhood at Handayani Kindergarten, Bombana Regency, (2) Improving language skills using storybook media in pre-school children at Handayani PAUD, Bombana Regency. This research uses a classroom action approach (PTK) with two cycles which have four stages, namely, planning, implementation, observation and reflection. The data collection techniques used are observation, documentation and assessment. The research results showed that as many as 12 children had language proficiency using storybooks as a very good assessment (BSB) with a completeness criterion of 91% or were in the good category. Thus, it is hoped that schools or teachers can apply more varied and innovative learning media so that children are more interested in the learning process.